THE CAREER READINESS AS A TEACHER ON UNIVERSITY STUDENTS BASED ON LOCUS OF CONTROL, SELF ESTEEM, AND PEDAGOGICAL COMPETENCE - RATNA Sari (Jurnal Psikologi TALENTA, 2019)
This research aims to determine the relationship of locus of control, self-esteem, pedagogical competence and career readiness to be a teacher on university students. The population of the research is students of IED at Universitas Muhammadiyah Yogyakarta. The sample is taken using incidental sampling technique. Data collection was conducted by using career readiness scale, locus of control scale, self-esteem scale, and pedagogical competence scale. The data are analyzed using statistical calculation method by using the multiple regressions technique. The results show that; (1) there is no  significant relationship between locus of control, self-esteem, pedagogical competence and career readiness to be a teacher, (2) there is a relationship between locus of control and career readiness to be a teacher, (3) there is no relationship between self-esteem and career readiness to be a teacher, (4) there is a correlation between pedagogical competence and career readiness to be a teacher. The total effective contribution of locus of control and pedagogical competence are 14.9%. The effective contribution of locus of control variable is 5.4% and pedagogical competence variable is 9.5%.